Prácticas de cazadores y recolectores nómadas en el mundo urbano - Canavessi, Juan José (Revista Segurança Urbana e Juventude, 2010)
This paper explores some of the relevant aspects of the following issue: present urban security through an anthropological and historical view. For this matter, it has been elaborated an ethnographic description of street-crime practice of teenagers and young people that belong from vulnerable communities of Buenos Aires - Gran Buenos Aires region, and also an analysis and interpretation of them on the basis of the historical process from the XIXth century onwards.